Coastal buffer and conservation zone management in the lower Mekong Delta, Vietnam : - Christensen, Stig Moller (Department of Economics and Natural Resources, 2003)
The four main scientific objects in this dissertation are: document and analyse the interactions, interdependencies, and conflicts between the local community dependent on natural resource within buffer and conservation zones of Damdoi forest enterprise,...